Crystal structure of 2-(4-ammoniocyclohexyl)-3-(pyridin-2-yl)imidazo[1,5-a]pyridin-2-ium 2-[(2-carboxylatophenyl)disulfanyl]benzoate dihydrate, [C18H22N4][C14H8O4S2] ⋅ 2H2O - Tan, Sang Loon *; Tiekink, Edward R. T. * (de Gruyter, 2019)
[C18H22N4][C14H8O4S2]·2H2O, orthorhombic, P212121 (no. 19), a = 9.7616(1) Å, b = 16.7411(2) Å, c = 18.6843(2) Å,V = 3053.39(6) Å3, Z = 4, Rgt(F) = 0.0265, wRref(F2) = 0.0679,T = 100(2) K. CCDC no.: 1902630 The crystal structure is shown in the figure. Tables 1 and 2 contain details on crystal structure and measurement conditions and a list of the atoms including atomic coordinates and displacement parameters.